Effect of oxygen partial pressure on properties of ZnO/Al thin films prepared by pulsed dc reactive magnetron sputtering with SpeedFlo controller. (28th March 2015) - Liu, C. Y.; He, F.; Zhang, Y. F.; Zang, S. G.; Zuo, Y.; Ma, J. R.
Abstract : Transparent conductive aluminium doped zinc oxide (ZnO: Al, AZO) films have been prepared on glass substrate by pulsed direct current reactive magnetron sputtering at room temperature. The dependence of oxygen partial pressure on the optical, electrical and structural properties was investigated. The oxygen partial pressure was accurately controlled by a closed loop SpeedFlo controller with a λ sensor. X-ray diffraction analysis indicated that the AZO films deposited at various oxygen partial pressures presented a polycrystalline wurtzite structure with a (002) preferred orientation perpendicular to the substrates. The densely packed AZO films with columnar structure were observed on the plan view by scanning electron microscope. The AZO film that was deposited at oxygen partial pressure of 3·36×10 −2 Pa has superior performance with minimal resistivity of 1·14×10 −3 Ω cm. Optical transmittance was obtained ∼80% in the visible region.